2017
DOI: 10.1002/jqs.3007
|View full text |Cite
|
Sign up to set email alerts
|

Sea ice, ice‐rafting, and ocean climate across Denmark Strait during rapid deglaciation (∼16–12 cal ka BP) of the Iceland and East Greenland shelves

Abstract: A suite of cores from the North-West Iceland and East Greenland shelves sampled fossiliferous or unfossiliferous basal glacial diamictons. Radiocarbon dates above the diamictons are similar on both shelves, but the value of the ocean reservoir correction, DR, is unknown. Deglaciation occurred either $16 or 14 cal ka BP depending on the choice of DR. The ice sheets were behind the present coastline by 12.2 cal ka BP. We examine seven cores that record the glacial/deglacial transition and present new data on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 149 publications
(247 reference statements)
0
14
0
Order By: Relevance
“…; Andrews et al . ), but tills also are commonly barren of dateable fossil material (Jennings ). The bulk density and shear strength of L1 were not measured, but the unit is noticeably compact, cracked and dense.…”
Section: Discussionmentioning
confidence: 99%
“…; Andrews et al . ), but tills also are commonly barren of dateable fossil material (Jennings ). The bulk density and shear strength of L1 were not measured, but the unit is noticeably compact, cracked and dense.…”
Section: Discussionmentioning
confidence: 99%
“…This is well constrained by 10 Be dating in coastal areas and 14 C dated marine cores in and outside major transect troughs, and applies to areas in western, eastern and southernmost Greenland (Fig 4). More recently this has been corroborated by new evidence from the Disko Bugt shelf (Hogan et al, 2016;Oksman et al, 2017) , and from east Greenland (Levy et al, 2016;Andrews et al, 2018;Dyke et al, 2018;Rainsley et al, 2018). However, this has recently been contested by evidence from multibeam bathymetry in major transverse troughs on the shelf, notably the occurrence of Grounding Zone Wedges (GZWs) as discussed below.…”
Section: Yd Ice-margins In Greenlandmentioning
confidence: 82%
“…Mörner and Funder, 1990), acknowledging that significant, but unknown, changes in the reservoir effect may potentially/likely have affected the ages especially in the turbulent millennia during the early deglaciation phases (e.g. Andrews et al, 2018).…”
Section: Field and Laboratory Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gray's map for April and May 1882 shows the ice encircling Iceland but, with Faxaflói ice free (Figure 1). Jennings, Andrews, and Wilson (2015) argued that icebergs from the Laurentide Ice Sheet reached southwest Iceland during the early Holocene and certainly the quartz wt% are also much higher in cores such as MD99-2256 and MD99-2259 immediately following deglaciation ( Figure 8D; Andrews et al 2018). Faunal and stable isotopic evidence in a push core (from box core HU93030-003; Jennings et al 2001) suggested colder ocean conditions during the Little Ice Age (LIA) and perhaps also indicating drift-ice transport into Faxaflói in the coastal current.…”
Section: Southwest Iceland Shelf: Faxaflóimentioning
confidence: 99%